Honey Dressing Versus Silver Sulfadiazene Dressing for Wound Healing in Burn Patients: A Retrospective Study - Gupta, Shilpi Singh (Medknow Publications & Media Pvt Ltd, 2011)
OBJECTIVE: The aim was to evaluate the effect of honey dressing and silver sulfadiazene (SSD) dressing on wound healing in burn patients. MATERIALS AND METHODS: We retrospectively reviewed the records of 108 patients (14–68 years of age), with first and second degree burns of less than 50% of the total body surface area admitted to our institution, over a period of 5 years (2004–2008). Fifty-one patients were treated with honey dressings and 57 with SSD. Time elapsed since burn, site, percentage, degree and depth of burns, results of culture sensitivity at various time intervals, duration of healing, formation of post-treatment hypertrophic scar, and/or contracture were recorded and analyzed. RESULTS: The average duration of healing was 18.16 and 32.68 days for the honey and SSD group, respectively. Wounds of all patients reporting within 1 h of burns became sterile with the honey dressing in less than 7 days while there was none with SSD. All wounds treated with honey became sterile within 21 days while for SSD-treated wounds, this figure was 36.5%. A complete outcome was seen in 81% of all patients in the “honey group” while in only 37% patients in the “SSD group.” CONCLUSION: Honey dressings make the wounds sterile in less time, enhance healing, and have a better outcome in terms of hypertropic scars and postburn contractures, as compared to SSD dressings.